If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(g + 5) = 5(g + -5) Reorder the terms: 4(5 + g) = 5(g + -5) (5 * 4 + g * 4) = 5(g + -5) (20 + 4g) = 5(g + -5) Reorder the terms: 20 + 4g = 5(-5 + g) 20 + 4g = (-5 * 5 + g * 5) 20 + 4g = (-25 + 5g) Solving 20 + 4g = -25 + 5g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-5g' to each side of the equation. 20 + 4g + -5g = -25 + 5g + -5g Combine like terms: 4g + -5g = -1g 20 + -1g = -25 + 5g + -5g Combine like terms: 5g + -5g = 0 20 + -1g = -25 + 0 20 + -1g = -25 Add '-20' to each side of the equation. 20 + -20 + -1g = -25 + -20 Combine like terms: 20 + -20 = 0 0 + -1g = -25 + -20 -1g = -25 + -20 Combine like terms: -25 + -20 = -45 -1g = -45 Divide each side by '-1'. g = 45 Simplifying g = 45
| 3(2x-9)-3=3(x-4)+9 | | (2i+2)(4i-5)=0 | | 0.3+0.5x=2.3+x | | 144=3x+47+7x-13 | | 10=6+lnx | | -3(2x)= | | -560+(-40)=-600 | | -5n-4=-94 | | -5y+15=6 | | -3(5p+4)-2(4-11p)=3(9+2p) | | -5+15=6 | | 6x^2+11a+2=4 | | X=-120+59 | | 18a^2-10a+27a-15=0 | | -2a+3-a=0 | | 9=3a | | 4-2x-3=17 | | 3x-6y-7x+3y= | | 2z-9=21 | | 9(y+9)= | | -d=-2d+7 | | 4+2x+3=17 | | C+28=c+65 | | ((30)180)+((36)180)+((((8)9)6)36)+((((8)5)6)36)+((((8)7)7)36)+(18(7))+8500= | | 19+4(6c-1)= | | 4+2x-3=17 | | 8x-9=6x+29 | | (6i+5)-(-10i-5)=0 | | 4(3x-3)-2=4(x-4)+42 | | 3y-6y+2=8y+6-5 | | 3x+4/2=5/6 | | 8x^3-120=0 |